TINJAUAN PERJANJIAN WARALABA SEBAGAI PERJANJIAN YANG DIKECUALIKAN DALAM PASAL 50 HURUF B UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT ( STUDI KASUS DI PT. BARAMA INTERCITY TREDUCASINDO ) - , Fatimah Samiyah, SH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this thesis is to find out the reasons why the franchise agreement in PT. Barama Intercity Treducasindo as agreements that are excluded in Article 50 letter b of Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition at once to find out if the franchise agreement made by PT. Barama Intercity Treducasindo has the potential violation of Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices and unfair business competition. The method used in this study is that normative legal research or literature and field research. Ways decomposition problems using deductive way of thinking, which collects research from the general to the things that are special to the study conducted by PT agreement. Barama Intercity Treducasindo. This study concluded that the Franchise Agreement For Excluded Agreement In Letter B of Article 50 of Law Number 5 Year 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition in the franchise agreement because it contained elements of Intellectual Property Rights as expressly . PT. Barama Intercity Treducasindo sebegai franchisees in the franchise agreement can be categorized as an agreement is excluded. It can be seen from one of the contents of the article 2 of article regulating the franchise agreement object that contains the brand, such as the name of the Barama Intercity following attributes attached.